Purification, crystallization and preliminary X-ray crystallographic analysis of diaminopimelate epimerase from Acinetobacter baumannii - Park, Jeong Soon (International Union of Crystallography, 2012)

(untitled)
The meso isomer of diaminopimelate (meso-DAP) is a biosynthetic precursor of l-lysine in bacteria and plants, and is a key component of the peptidoglycan layer in the cell walls of Gram-negative and some Gram-positive bacteria. Diaminopimelate epimerase (DapF) is a pyridoxal-5′-phosphate-independent racemase which catalyses the interconversion of (6S,2S)-2,6-diaminopimelic acid (ll-DAP) and meso-DAP. In this study, DapF from Acinetobacter baumannii was overexpressed in Escherichia coli strain SoluBL21, purified and crystallized using a vapour-diffusion method. A native crystal diffracted to a resolution of 1.9 Å and belonged to space group P3(1) or P3(2), with unit-cell parameters a = b = 74.91, c = 113.35 Å, α = β = 90, γ = 120°. There were two molecules in the asymmetric unit.